Association Between Life Events and Rheumatoid Arthritis: Results From a Population‐Based Case–Control Study. Issue 6 (June 2014) - Wesley, Annmarie; Bengtsson, Camilla; Skillgate, Eva; Saevarsdottir, Saedis; Theorell, Töres; Holmqvist, Marie; Klareskog, Lars; Alfredsson, Lars; Wedrén, Sara; for the EIRA Study Group
<x xml:space="preserve">Abstract</x> Objective To investigate the association between life events and the risk for rheumatoid arthritis (RA) with and without antibodies to citrullinated protein (ACPAs). Methods We used data from a population‐based case–control study of individuals ages 18–70 years living in geographically defined parts of Sweden between May 1996 and November 2009. We included incident cases (n = 2, 774) diagnosed by rheumatologists according to the American College of Rheumatology 1987 criteria for RA and randomly selected controls (n = 3, 911) matched to the cases by age, sex, and area of residence. All of the participants answered a questionnaire consisting of questions about 15 life events. We calculated odds ratios (ORs) and 95% confidence intervals (95% CIs) from unconditional logistic regression models adjusted for matching variables and confounding factors. Results Having experienced a life event was weakly associated with ACPA‐positive RA as well as ACPA‐negative RA (OR 1.1, 95% CI 1.0–1.2 and OR 1.2, 95% CI 1.0–1.4, respectively). The association with ACPA‐negative RA was stronger with an increasing number of events (OR 1.4, 95% CI 1.1–1.7 for having experienced ≥3 events versus none). Several particular life events were associated with RA (e.g., "conflict at work, " "change of residence, " "change of work place, " and "increased responsibility at work"). The results were more consistent in women than in men. Conclusion Our study lends support to the concept that certain stressful conditions, here measured as life events, are associated with an increased risk of developing RA.